2017
DOI: 10.3233/cbm-160659
|View full text |Cite
|
Sign up to set email alerts
|

Screening of exosomal microRNAs from colorectal cancer cells

Abstract: Colorectal cancer cells secrete a large number of miRNAs within exosomes. miR-379 decreases cell proliferation and migration, and miR-379 enriched exosomes can be engineered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…These miRNAs are also elevated in serum-derived EVs of CRC patients [76]. Other studies have also found miR-1246 to be upregulated in EVs derived from a number of in vitro cell lines [78,86]. Additionally, Ji et al found elevation of miR-19a and miR-203a in A33-positive EVs isolated from CRC cell line culture compared to CRC cell lysate.…”
Section: Ev-mirnas In Crc Cell Lines and Tumour Tissuementioning
confidence: 93%
“…These miRNAs are also elevated in serum-derived EVs of CRC patients [76]. Other studies have also found miR-1246 to be upregulated in EVs derived from a number of in vitro cell lines [78,86]. Additionally, Ji et al found elevation of miR-19a and miR-203a in A33-positive EVs isolated from CRC cell line culture compared to CRC cell lysate.…”
Section: Ev-mirnas In Crc Cell Lines and Tumour Tissuementioning
confidence: 93%
“…To confirm the presence of EVs, morphological examination of fixed EVs embedded in resin was performed as previously described [26]. Briefly, a primary fixative (2% glutaraldehyde, 2% paraformaldehyde in a 0.1 M sodium cacodylate/HCL buffer, pH 7.2) was added to samples prior to ultracentrifugation, and following isolation, EVs were immersed in a secondary fixative (1% osmium tetroxide), dehydrated in alcohol, and embedded in resin.…”
Section: Characterisation Of Extracellular Vesiclesmentioning
confidence: 99%
“…Briefly, a primary fixative (2% glutaraldehyde, 2% paraformaldehyde in a 0.1 M sodium cacodylate/HCL buffer, pH 7.2) was added to samples prior to ultracentrifugation, and following isolation, EVs were immersed in a secondary fixative (1% osmium tetroxide), dehydrated in alcohol, and embedded in resin. Resin slices were then loaded onto a copper grid, stained, and viewed using an Hitachi H7000 transmission electron microscope [26].…”
Section: Characterisation Of Extracellular Vesiclesmentioning
confidence: 99%
“…For example, miR‐375 targets genes that play a key role in regulating signaling pathways, such as mitogen‐activated protein kinase, Wnt, TGF‐β, and by these ways, it results in inhibition of CRC progression . Moreover, miR‐379 in HT‐29 and HCT‐116, as two well‐known CRC cell lines, also decreases cell proliferation and migration …”
Section: Exosomes In Crc Progressionmentioning
confidence: 99%
“…53,54 Moreover, miR-379 in HT-29 and HCT-116, as two well-known CRC cell lines, also decreases cell proliferation and migration. 55 Furthermore, the study of plasma samples from patients with CRC and also SW480 and WiDr cell lines in vitro has shown that miR-21, as a CRC-derived exosomal miRNA, can promote cell proliferation and progression and also can induce CRC metastasis and, therefore, it can be used as a poor prognosis CRC biomarker. 56 Studies related to the functions of different miRNAs in CRC-derived exosomes are summarized in Table 2.…”
Section: Exosomes In Crc Progressionmentioning
confidence: 99%